Schizophrenie des Kindes- und Jugendalters - Eggers, Christian (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2011)
Childhood schizophrenia is a rare but clinically difficult form of schizophrenia. Early childhood schizophrenia should be diagnosed as early as possible, also because of the poor prognosis. The new book by schizophrenia expert Christian Eggers comprehensively conveys the symptoms, the course characteristics and the prognosis of schizophrenia in childhood and adolescence. Other focal points of the book are the presentation of thinking and language disorders in childhood schizophrenia, detailed differential diagnostic discussions (with case studies) and the premorbid development, as well as early warning and precursor symptoms, mortality and the importance of post-psychotic personality and personality changes. The stigmatization caused by the environment or the delinquency and forensic significance of schizophrenia in childhood and adolescence is also discussed. Etiological findings and hypotheses and the resulting therapeutic, socio-educational, rehabilitative and preventive conclusions are presented in detail. One focus is on the close interlinking between modern (molecular) genetic findings and environmentally dependent and life history constellations. The presentation is based on the author's outstanding scientific work with his worldwide unique sample of the course of the disease of children with schizophrenia, which were personally examined by the author after an average of 15 and 42 years. With the book, the author also documents his extensive practical experience from many decades of clinical activity, which focuses on the schizophrenia of childhood and adolescence.